Transformasi Pendidikan Agama Islam di Era Digital: Implementasi Literasi Digital dalam Pembelajaran di Wilayah Banyumas - Muhamad Slamet Yahya (LP. Ma'arif Janggan Magetan, 2023)
This study aims to analyze the implementation of digital literacy in learning Islamic Religious Education in Banyumas through planning and implementation. Against the background of the need for the development of digital literacy skills for students in facing the digital era, this study identifies structured planning and implementation that involves technology and digital media as important factors in increasing learning effectiveness. The research method used is a case study involving SMK Negeri 1 Kaligondang as a research subject. The results of the study show that good planning and implementation that is integrated with technology have had a positive impact in improving the quality of Islamic Religious Education learning, preparing students to face technological changes, and enriching their understanding of Islam. The conclusions from this study emphasize the urgency of implementing digital literacy in learning Islamic Religious Education in Banyumas as an effort to optimize the use of technology and digital media in enhancing Islamic religious learning that is relevant to students' lives in this digital era.